أنموذج تمكين القوة الناعمة بين دولتين - الأورفلي, خضر; حاووط, عزّ الدين (Latakia University Journal - Economic and Legal Sciences Series, 2016)
This research is an attempt to introduce the concept of soft power through simple model of how it going to be empowerment, Aside to show every stage of empowerment processes, beginning displays Find concept of soft and definition of power, then the scientific importance, which is trying to illustrate the growing importance of soft in the modern international relations of force with highlight on the causes of this growing scientific interest and practical interest in this concept, the following, the analytical presentation of the relationship between hard power and soft power, then researcher shows four models of how soft power get empowerment and structure it between two states, finally results and discussion.هذا البحث هو محاولة لطرح مفهوم القوة الناعمة عبر نموذج مبسط لعملية تمكينها، من خلال تفسير كل مرحلة من مراحلها التي تُشكل ظاهرة لقوة الدولة، إضافة إلى اقتراح استراتيجيات مفيدة للوصول لنموذج جيد لها. بداية يعرض البحث الأهمية العلمية التي تحاول توضيح تنامي أهمية القوة الناعمة في العلاقات الدولية الحديثة, مع تسليط الضوء على مسببات تنامي هذه الأهمية العلمية والاهتمام العملي بهذا المفهوم،بناء عليه فإنه يعطي مدخلا منهجيا لعملية القوة الناعمة في سياق أوجه القوة البارزة في أدبيات القوة، ومن ثم، عرض لتحليل العلاقة بين القوة الصلبة والقوة الناعمة، ثم يتم الانتقال لتقديم ربط أكثر وضوحاً للقوة الناعمة على شكل أكثر تمثيلاً وتبسيطاً لمخطط عملية تمكين القوة الناعمة، أخيراً يتم عرض النتائج ومناقشتها والاستراتيجيات المستنتجة لاتخاذ القرارات المهمة والضرورية للتوظيف الفعال لآليات القوة الناعمة.